2021
DOI: 10.3389/fmicb.2021.659613
|View full text |Cite
|
Sign up to set email alerts
|

mcr-1 Identified in Fecal Escherichia coli and Avian Pathogenic E. coli (APEC) From Brazil

Abstract: Colisitin-associated resistance in bacteria of food producing animals has gained significant attention with the mcr gene being linked with resistance. Recently, newer variants of mcr have emerged with more than nine variants currently recognized. Reports of mcr associated resistance in Escherichia coli of poultry appear to be relatively limited, but its prevalence requires assessment since poultry is one of the most important and cheapest sources of the world’s protein and the emergence of resistance could lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 54 publications
(46 reference statements)
2
18
0
Order By: Relevance
“…As colistin has been a last-resort antimicrobial for defending against MDR Gram-negative bacteria, we are surprised to see the high detection rate of mcr-1 in Salmonella from food products. Given mcr-1 has been found in Salmonella from animals in many countries [ 6 , 53 ] and also occurred in Salmonella of human origin [ 17 , 19 ], food products, especially fresh eggs, may play a key role in disseminating such pathogens between animals and humans. In this study, all the mcr-1 -positive Salmonella isolates were ST34 S .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As colistin has been a last-resort antimicrobial for defending against MDR Gram-negative bacteria, we are surprised to see the high detection rate of mcr-1 in Salmonella from food products. Given mcr-1 has been found in Salmonella from animals in many countries [ 6 , 53 ] and also occurred in Salmonella of human origin [ 17 , 19 ], food products, especially fresh eggs, may play a key role in disseminating such pathogens between animals and humans. In this study, all the mcr-1 -positive Salmonella isolates were ST34 S .…”
Section: Discussionmentioning
confidence: 99%
“…The mcr-1 gene has been reported in plasmids with different replicon types including IncI2, IncX4, IncHI2, IncHI1, IncP, IncFII and IncFIB [ 1 , 17 ], and the primary replicon type varies among different Enterobacteriaceae members. For instance, IncI2 and IncX4 were the two primary replicon types of plasmids harboring mcr-1 in E. coli from animals [ 6 ] and humans [ 5 ]. However, mcr-1 -carrying IncHI2 plasmid was the primary type in Salmonella from animals [ 57 ] and humans [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmid pL889-MCR1 is a 63,050 bp circular plasmid belonging to IncI2, which was associated with the global dissemination of MCR-1-producing E. coli from animal and human sectors. [27][28][29][30][31] Nucleotide sequence alignment indicated that it aligned very well to plasmids pHNTH02-1 (KY693674), pHLJ179-34 (MN232213), and p5CRE51-MCR-1 (CP021176) (Figure 2B). Of note, p5CRE51-MCR-1 carrying isolate was recovered from a urinary tract infection, which represents the first case reported an E. coli strain co-producing MCR-1 and NDM-9.…”
Section: Dovepressmentioning
confidence: 87%
“…An MDR and ESBL-producing ST711 E. coli carrying a new mcr -5 variant, named mcr -5.3 on a novel 5361 bp plasmid, was isolated from the lung tissue of a horse that never received COL and died of pneumonia in 2012 in Brazil [ 55 ], suggesting that E. coli that co-produces MCR-5 and ESBL has been present in South America for at least almost a decade and is associated with difficult-to-treat diseases in horses. The mcr -5 gene has been detected in E. coli isolates from poultry birds in Brazil [ 80 ]. The livestock sector could be the source of mcr -5 in the Brazilian equine sector since massive amounts (up to 10 g/ton of feed) of polymyxins/COL was used in livestock feed as a growth enhancer in Brazil [ 81 ].…”
Section: Epidemiology and Traits Of Mcr -Gene-bear...mentioning
confidence: 99%